Fatigue Management Through Aerobic Physical Exercise in Children with Acute Lymphoblastic Leukemia (ALL) : A Literature Review - Ikeu Nurhidayah; Asti Oktovianti; Guztap Jabarul Haq; Nur Oktavia Hidayati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Cancer related fatigue (CRF) is a serious symptom and often appears in pediatric patients with ALL, during chemotherapy and also at the end of treatment. The aim of this literature study is to look at physical exercises that can be done to reduce fever symptoms in pediatric patients with ALL. This research uses literature study with descriptive type of study. Obtained 3 articles using keywords, articles were obtained from Google Scholar, Proquest, and Pubmed. The three articles published between 2011-2021 with the research methods of each article were randomized controlled trials (RCTs) and quasi-experimental. Based on the results of several research articles, it was found that physical exercise combined with aerobics was proven to be effective in dealing with fatigue, increasing muscle strength and improving the quality of life of pediatric patients with ALL. This is consistent with studies that the advantage of physical exercise is hypertrophy, namely an increase in the mass of muscle cells that is triggered by neural factors in a repetitive exercise program. Meanwhile, aerobic exercise is related to the function of the respiratory system and stroke volume. This is consistent with studies that the advantage of physical exercise is hypertrophy, namely an increase in the mass of muscle cells that is triggered by neural factors in a repetitive exercise program. Meanwhile, aerobic exercise is related to the function of the respiratory system and stroke volume. Keywords: Children, Acute Lyphoblastic Leukemia (ALL), Pyhsical Exercise, Muscle Strength